Navigating Progress and Obstacles in Indonesia’s Sharia Capital Market - Samudra, Gilang (Journal of Economicate Studies, 2025)
The Islamic capital market in Indonesia has evolved from its colonial roots into a dynamic financial system grounded in sharia principles. This study examines the development, prospects, and challenges of Indonesia’s Islamic capital market within the framework of Maqasid al-Shariah, stakeholder theory, and market efficiency. Using qualitative analysis and a review of recent empirical findings, the research highlights significant growth in sharia-compliant instruments, investor participation, and regulatory innovation, particularly under the OJK Roadmap 2020–2024. However, persistent challenges remain, including limited product diversity, regulatory overlap, and low financial literacy. The study underscores the need for ethical integration, technological innovation, and institutional synergy to ensure sustainable and inclusive market expansion. The findings contribute to strengthening the theoretical and practical foundations of Islamic finance as a pillar of Indonesia’s economic resilience and moral economy.